Morbidity Pattern Study among Pregnant Women Attending Antenatal Clinic at Community Health Centre - Suthar, Jalpa; Patel, Kripa (Indian Journal of Pharmacy Practice)
Background: About half a million women die every year of causes related to obstetrics complication. Complication can arise at any time during pregnancy; child birth and post natal period and in absence of intervention, there is a high feto-maternal morbidity and mortality. The aim of the study was to know the morbidity pattern and pregnancy outcome among the antenatal attending to the community health centre. Method: A prospective observational study was conducted on pregnant women during August 2013 to December 2013. Data regarding maternal socio-demographic profile and antenatal profile was collected. Results: A total 512 pregnant women attended the health centre of whom, 88.87% patients had at least one morbidity pattern or complain. In our study moderate anemia (65.26%), severe anemia (13.79%) and pregnancy induced hypertension (4.78%) were the most common morbidities. Further, morbidity pattern like, pregnancy associated common complains, mild anemia abnormal presentation, abortion, preterm labor, oligohydramnios, urinary tract infection and HIV were also reported. Conclusion: Maternal morbidity is notably high, although most of the common problems were not lifethreatening. They are more likely to have marked influence on their well-being and health status in the long run. Most conditions could be addressed through provision of health promotion and preventive interventions.
Keywords: Antenatal; Obstetric complication; Outcome of pregnancy; Pregnancy